K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 9 2020

Sửa đề lại tí cho chuẩn nha: a+b+c=0, tính R = (a-b)c+ (b-c)a3 + (c-a)b3

R = ac3 - bc+ ba3 - ca3 + cb3 - ab= ab(a2-b2) + ac(c2-a2) + bc(b2-c2

                                                          = ab(a-b)(a+b) + ac(c-a)(a+c) + bc(b-c)(b+c)

Thay a+b=-c, b+c=-a, c+a=-b vào -->R = abc(b-a) + abc(a-c) +abc(c-b) = abc(b-a+a-c+c-b) = 0

30 tháng 6 2018

Ta có A=\(\left(ab+bc+ca\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)-abc\left(\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}\right)\)

=\(2\left(a+b+c\right)+\frac{ab}{c}+\frac{bc}{a}+\frac{ca}{b}-\frac{ab}{c}-\frac{bc}{a}-\frac{ca}{b}=2\left(a+b+c\right)\)

30 tháng 6 2018

\(A=\left(a+b\right)\left(a^2-ab+b^2\right)+3ab\left[\left(a+b\right)^2-2ab\right]+6a^2b^2=a^2-ab+b^2+3ab\left(1-2ab\right)+6a^2b^2\)

=\(\left(a+b\right)^2-3ab+3ab-6a^2b^2+6a^2b^2=1\)

2) Ta có \(A=\left(a-1\right)\left(b-1\right)\left(c-1\right)=abc-ab-bc-ca+a+b+c-1=0\)